Reduction of Textile Industrial Waste water Pollution - Ahmed, Mutasim Abdalla (Gezira Journal of Engineering and Applied Sciences, 2018)
The purpose of this study is to evaluate the environmental performance and the impacts of the textile waste water from wet processing, and to find some approaches for pollution prevention or reduction . Taha Textile Mill at Khartoum North is taken as a case. The study includes the important parameters affecting pollution overload associated with the wet processing stages, such as, desizing, scouring, bleaching, dyeing, finishing and washing . Different industrial wastewater samples were taken at different intervals of time, and subjected to various tests, and analytical methods. The study proved that, the extensive use of chemicals, dyestuffs and water results in generation of highly polluted water differing in magnitude and quality, such as: COD, BOD, turbidity, heavy metals, anions, alkalinity, color, pH, TDS, electrical conductivity, strong smelling, high temperature, etc. When the obtained results are compared with some international standards such as (U.S EPA), Pakistan (NEQS); it is found that, they mostly exceed these international standard limits. The study proved that, pollution can be reduced by reduction of water consumption such as: effluent reuse, discoloration, precipitation with metal salts, carbon adsorption, oxidation, etc. The study proved that, dye bath from vat and sulfur dyes can be reused for four times; the obtained shades and color fast nesses are both good. High reduction in both color concentration of the residual wastewater and pH is obtained, which will indicate that the other pollution parameters such as COD, BOD, TDS, etc. are reduced.